Establishing regularities of fire protection of wood by a composite coating with a biopolymer - Tsapko, Yuriy; Tsapko, Aleksii; Likhnyovskyi, Ruslan; Bielikova, Kseniia; Berdnyk, Oksana; Gavryliuk, Andrii; Borysova, Anna; Dotsenko, Oleksandr; Haiduk, Maksym; Nesterenko, Viacheslav (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is changes in the surface properties of wood during its treatment with a fire-retardant composite coating with the presence of biopolymers. The task, aimed at the production of environmentally friendly compositions obtained from natural and renewable sources for fire protection of wood and the application technology, is to ensure resistance to the action of high-temperature flames. It has been proven that the fire-retardant composition with the presence of biopolymers is an accumulation of biological substances with nitrogen-phosphorus flame retardants, carbohydrates, and gas-forming substances, bordered by a polymer binder. Under the influence of thermal action, chemical reactions begin in the fire-retardant composition, ammonium polyphosphate decomposes and releases phosphoric acid. This, in turn, affects the destruction of the biopolymer and the dehydration of pentaerythritol with the formation of a large amount of hydrocarbons, and melamine causes the release of non-combustible gases, which induce the formation of foam coke. A study of the surface energy characteristics of the fire-retardant composition with the presence of biopolymers was carried out and it was found that the polarity of the fire-retardant composition with the presence of biopolymers exceeds the value of untreated wood by 3.5 times, which provides effective treatment of the wood surface. According to the results of thermal exposure to the samples, it was found that under the action of the radiation panel, the fire-retardant composition swelled, when biopolymers such as wood flour and starch were added, the coke height increased by more than 15 mm, and the foam multiplicity increased by 1.2 times. The practical significance is that the results were taken into account when designing a reactive coating for wood. Thus, there is reason to argue about the possibility of effective protection of wood with a fire retardant composition with the presence of biopolymers